Aging-Related Oxidative Stress: Positive Effect of Memory Training. (1st February 2018) - Pesce, Mirko; Tatangelo, Raffaella; La Fratta, Irene; Rizzuto, Alessia; Campagna, Giovanna; Turli, Cinzia; Ferrone, Alessio; Franceschelli, Sara; Speranza, Lorenza; Patruno, Antonia; Ballerini, Patrizia; De Lutiis, Maria Anna; et al.
Highlights: Memory training increases global cognitive functioning in healthy elderly. Memory empowerment reduces systemic oxidative burden after 6 months of progressive training. Memory training increases antioxidant potential in healthy elderly. Abstract: The cognitive impairment characterizing the phenotype of older adults has been related to the efficiency of the antioxidant system. This study aimed at investigating the effect of memory training (MT) on memory, global cognitive functioning, and the oxidant and antioxidant capacity of plasma. We recruited 52 healthy subjects aged over 60. Twenty-nine subjects were submitted to 6-months of MT (Experimental Group, EG), and 23 were used as a Control Group (CG). Global cognitive functioning was assessed by the Mini-Mental State Examination (MMSE) and Short- and Long-Term Memory (STM and LTM, respectively) by the Rey Auditory Verbal Learning Test (RAVLT) at baseline (T0) and after 6-months (T1). Meanwhile, Reactive Oxygen Metabolites derivative compounds (d-ROMs), Biological Antioxidant Potential (BAP), and their ratio were evaluated on plasma. Results showed that the MMSE and RAVLT scores improved in EG at T1. At the same time, the d-ROMs levels significantly decreased, while the BAP and BAP/d-ROMs ratio showed an opposite trend. In both groups, the MMSE and LTM scores were negatively associated with d-ROMs levels, and positively correlated with BAP levels and the BAP/d-ROMs ratio. When we considered the Δvalue (Δvariable = variable post-MT minus variable pre-MT) in EG, the ΔMMSE and ΔLTM scores were negatively associated to Δd-ROMs, and positively to ΔBAP and ΔBAP/dROM. In conclusion, our results suggest that MT improves memory and global cognitive functioning. These processes were significantly associated to increase in resistance against oxidative stress at the plasma level in healthy older adults.